PENGARUH SIKAP KEWIRAUSAHAAN, NORMA SUBJEKTIF, DAN PENGETAHUAN KEWIRAUSAHAAN TERHADAP NIAT WIRAUSAHA MAHASISWA - William Ekachandra; Ida Puspitowati (Jurnal Manajemen, 2022)
Indonesia's the fourth most populous country in the world and the first in Southeast Asia in 2022. However, the ratio of the number of entrepreneurs in Indonesia is inversely proportional to the population. This study aims to empirically examine the effect of entrepreneurship attitudes, subjective norm, and entrepreneurship knowledge on students' entrepreneurship intentions. This study uses a quantitative research design with a descriptive correlational approach and purposive sampling. The 112 respondents from Universitas Tarumanagara S1 Management students who have received entrepreneurship education answered the instrument on this research survey questionnaire. Data were processed using SmartPLS 4 software with data analysis, such as validity and reliability tests; coefficient of determination; effect size; and bootstrap hypothesis testing. The results of the study stated that entrepreneurship attitudes and subjective norm had shown to be positive and significant, while entrepreneurship knowledge had positive and insignificant result toward entrepreneurship intention. This research is expected to be a reference for similar research in the future by developing and applying research variables, such as entrepreneurship knowledge, as well as the scope of the sample can be expanded to obtain more diverse information.